Pain, Physical Function, Radiographic Features, and Quality of Life in Knee Osteoarthritis Agricultural Workers Living in Rural Population - Gordana Nikolic; Biserka Nedeljkovic; Goran Trajkovic; Dragisa Rasic; Zlatica Mirkovic; Slavica Pajovic; Rade Grbic; Sandra Sipetic; Isidora Vujcic (Pain Research and Management)
Background. The aim of this study was to analyse the relationship between the clinical manifestations, disease severity based on radiography images, functional activity level, and quality of life in patients with knee osteoarthritis in a rural population living in Serbian enclaves in Kosovo, as well as to determine the correlation between the WOMAC and the EQ-5D questionnaire in this population. Method. The cross-sectional study was conducted at the Internal Medicine Clinic, Clinical Hospital Center Pristina-Gracanica, located in Laplje Selo from February to December 2013. One hundred patients with confirmed (American College of Rheumatology criteria) knee osteoarthritis completed the EQ-5D and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaires, rated pain on a visual analogue scale (VAS), and underwent knee radiographic examinations. Result. Most patients were obese with moderate radiographic changes according to the Kellgeren–Lawrence scale and suffered from very severe pain according to the VAS scale. The duration of disease significantly correlated with the WOMAC scores, VAS score, and all of the scores on the EQ-5D, except for mobility. The age of participants showed a similar correlation with the same variables. The patients with higher Kellgren–Lawrence scores (3-4) were significantly older, with a significantly higher body mass index (BMI) and longer duration of disease than patients with lower scores (1-2). Significantly higher VAS, pain/discomfort EQ-5D, and WOMAC pain and function scores were also recorded among patients with more significant radiological changes. The correlations between WOMAC and EQ-5D were satisfactory. Conclusion. The severity of clinical manifestations and radiographic area changes may affect functional ability and the quality of life in knee OA patients living in rural areas, which requires adequate treatment and physical therapy.